Sentiment analysis to determine employee job satisfaction using machine learning techniques - Mouli, Nazifa; Das, Protiva; Bin Muquith, Munim; Biswas, Aurnab; Kabir Niloy, MD Dilshad (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.